Epigenetically Modified Bone Marrow Stromal Cells in Silk Scaffolds Promote Craniofacial Bone Repair and Wound Healing - Han, Qianqian (Tissue Eng Part A, 2015)
Epigenetic regulation of gene expression is a central mechanism that governs cell stemness, determination, commitment, and differentiation. It has been recently found that PHF8, a major H4K20/H3K9 demethylase, plays a critical role in craniofacial and bone development. In this study, we hypothesize that PHF8 promotes osteoblastogenesis by epigenetically regulating the expression of a nuclear matrix protein, special AT-rich sequence-binding protein 2 (SATB2) that plays pivotal roles in skeletal patterning and osteoblast differentiation. Our results showed that expression levels of PHF8 and SATB2 in preosteoblasts and bone marrow stromal cells (BMSCs) increased simultaneously during osteogenic induction. Overexpressing PHF8 in these cells upregulated the expression of SATB2, Runx2, osterix, and bone matrix proteins. Conversely, knockdown of PHF8 reduced the expression of these genes. Furthermore, ChIP assays confirmed that PHF8 specifically bound to the transcription start site (TSS) of the SATB2 promoter, and the expression of H3K9me1 at the TSS region of SATB2 decreased in PHF8 overexpressed group. Implantation of the BMSCs overexpressing PHF8 with silk protein scaffolds promoted bone regeneration in critical-sized defects in mouse calvaria. Taken together, our results demonstrated that PHF8 epigenetically modulates SATB2 activity, triggering BMSCs osteogenic differentiation and facilitating bone formation and regeneration in biodegradable silk scaffolds.